Properties of High Na-Ion Content N-Propyl-N-Methylpyrrolidinium Bis(Fluorosulfonyl)Imide -Ethylene Carbonate Electrolytes. (1st September 2017) - Noor, S.A.M.; Su, N.C.; Khoon, L.T.; Mohamed, N.S.; Ahmad, A.; Yahya, M.Z.A.; Zhu, H.; Forsyth, M.; MacFarlane, D.R.
Abstract: Sodium-based batteries have emerged as promising alternatives to Li-based batteries for future safe, high energy-density energy storage. They are expected to be cheaper, due to the greater abundance of Na and likely reduction in raw material costs. In this study, we investigate the properties of superconcentrated sodium bis(fluorosulfonyl)amide (NaFSI) mixtures with the ionic liquid (IL) methylpropylpyrrolinium (C3 mpyr) FSI in the presence of ethylene carbonate (EC) in the liquid and gel states. Ionic conductivity and thermal stability are evaluated through electrochemical impedance spectroscopy (EIS) and differential scanning calorimetry (DSC), respectively. NaFSI is soluble in the IL up to 55 mol% Na; adding EC (30 wt.%) to the IL almost doubles the ionic conductivity at ambient temperature. The temperature dependence of conductivity is well described by the Vogel-Tamman-Fulcher equation. NMR spectroscopy and Pulse Field Gradient NMR diffusion were employed to investigate transport in these electrolyte systems, while the chemical interactions were also studied using ATR-FTIR. Stable plasticized gel electrolytes were observed, even at 30 wt. % EC; the formation of the gel does not significantly affect the liquid-like ion dynamics in these materials, as shown by DSC and FTIR analysis. The Na + transference number of Na0 .55 [C3 mpyr]0.45 [FSI] + 30 wt.% EC was up to 0.32, and deposition and dissolution of sodium metal were observed in cyclic voltammetry around 0 V vs. Na/Na + . Moreover, the suitability of the prepared electrolyte is preliminarily verified in half-cells at room temperature using Na3 V2 (PO4 )3 as a cathode. The cells delivered capacity of 52.4 mAhg −1 at C/20.